Analysis of Growth and Establishment of Eucalyptus Camaldulensis in the Indian Arid Zone - Muthana, K D; Ramakrishna, G V.S; Arora, G D (Annals of Arid Zone, 2016)
Studies on Eucalyptus comaldulensis indicated that there is no signifcant effect of fertilizer or weeding singly or in combination of each other in the Indian arid zone. Trend curves fitted to the growth-in-plant height and Diameter at Breast Height (DBH) indicated that the plant can attain a height of 1155.85 cm in these areas. Further, sixty per cent establishment of the plant is estimated in these regions.